Data transmission at millimeter waves : exploiting the 60 GHz band on silicon /: exploiting the 60 GHz band on silicon. (2015) - Khalaf, Khaled; Vidojkovic, Vojkan, 1974-; Wambacq, Piet; Long, John R (John Robert), 1958-
No abstract available